1995
DOI: 10.1002/app.1995.070570104
|View full text |Cite
|
Sign up to set email alerts
|

Soluble aromatic polyimides and polyamides based on 4,4′‐diaminotriphenylmethane

Abstract: SYNOPSISAromatic polyamides and polyimides were synthesized from 4,4'-diaminotriphenylmethane (DA-TPM) for studying their solubility, thermal, and mechanical properties. The polymers were found to be soluble in amide solvents and pyridine, and this could be attributed to the practically free rotation of the polymer chain segments around the bridging group within the DA-TPM and the effect of its pendant phenyl ring. The polyimides and polyamides exhibited well-distinguished glass transition in the range of temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…17 For PI-TPMs obtained from the chemical imidization of PAA or from the one-step high-temperature polycondensation, the inherent viscosity ranged from 0.4 to 1.4 dL/g depending on the structure of the anhydride moiety. 2,3 The molecular weight of PMDA-ODA was characterized by measuring the inherent viscosity of the corresponding precursor PAA (0.5 g/dL DMF solutions at 25°C). The obtained inh was 2.5 dL/g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…17 For PI-TPMs obtained from the chemical imidization of PAA or from the one-step high-temperature polycondensation, the inherent viscosity ranged from 0.4 to 1.4 dL/g depending on the structure of the anhydride moiety. 2,3 The molecular weight of PMDA-ODA was characterized by measuring the inherent viscosity of the corresponding precursor PAA (0.5 g/dL DMF solutions at 25°C). The obtained inh was 2.5 dL/g.…”
Section: Resultsmentioning
confidence: 99%
“…The monomer 4,4-diaminotriphenylmethane (DA-TPM) was prepared by the reaction of aniline with benzaldehyde at 140°C under a nitrogen flow. 2,3,10,11 Polymer-grade DA-TPM (mp 126°C) was obtained by repeating the recrystallization of the crude product from benzene followed by sublimation at 110°C and 10 Ϫ4 mmHg.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…4-4'-Diaminotriphenylmethane (DA-TPM) and its derivates, have attracted the attention of our research group as monomers for the synthesis of various rigid-rod polyamides (PAs) and PIs. [23,24] The pendant phenyl ring and practically free internal rotation of the triphenylmethane bridging group predicted from the theoretical calculations make DA-TPM an excellent candidate for synthesis of processable PAs and PIs without sacrificing the high thermal stability. [23] Earlier research carried out for the structurally similar N,N-diamine triphenylamine (DA-TPA) showed that the incorporation of a pendant phenyl group into the polymer backbone is a successful approach to increase solubility and processability of PIs.…”
Section: Introductionmentioning
confidence: 99%